Evaluasi Usability Pada Aplikasi M-paspor Menggunakan System Usability Scale (SUS): Usability Evaluastion On M-passport Application Using System Usability Scale (SUS) - Resi delia viradila aji; Marlinda Sanglise; Lion Ferdinand Marini (Universitas Papua, 2025)
Rapidly developing information technology has given rise to many facilities to facilitate people's activities in their daily lives. Therefore, several public service agencies have begun to develop information technology to manage and serve the public to be more efficient and effective, one of which is the Immigration office releasing the M-passport application for making passports online. so it is necessary to examine user satisfaction of the M-passport application. This study is a quantitative study using the System Usability Scale (SUS) method which is used to measure the level of satisfaction of M-passport application users. The results of the study of 20 respondents obtained a score of 62 with an Acceptability range entering the